1984
DOI: 10.1007/bf00217162
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical identification of CRF-like and SRIF-like peptides in the brain and the pituitary of cyprinid fish

Abstract: Single and double immunocytochemical techniques were applied to the brain and pituitary of carps and goldfish. With the use of antiserum raised against synthetic corticotropin-releasing factor (CRF), immunoreactive perikarya were observed in the nucleus praeopticus and the nucleus praeopticus periventricularis. CRF-like-immunoreactive hypothalamic nerve fibers reach the pituitary. In cyprinids, some fine fibers enter the rostral neurohypophysis bordered by prolactin- and ACTH cells. Other thicker fibers extend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(19 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…In the telencephalon, a moderate number of immunoreactive perikarya was found in the medial subpallium of the lungfish (this study) and the frog Andersen et al, 1992), whereas in teleost fish, somatostatin-containing neurons have been observed in the nucleus entopeduncularis of tilapia (Grau et al, 1985), carp, and goldfish (Olivereau et al, 1984b). In the telencephalon of mammals, somatostatin-immunoreactive neurons are far more widely distributed than in other vertebrate groups.…”
Section: Comparative Distribution Of Somatostatin-containing Neurons mentioning
confidence: 67%
“…In the telencephalon, a moderate number of immunoreactive perikarya was found in the medial subpallium of the lungfish (this study) and the frog Andersen et al, 1992), whereas in teleost fish, somatostatin-containing neurons have been observed in the nucleus entopeduncularis of tilapia (Grau et al, 1985), carp, and goldfish (Olivereau et al, 1984b). In the telencephalon of mammals, somatostatin-immunoreactive neurons are far more widely distributed than in other vertebrate groups.…”
Section: Comparative Distribution Of Somatostatin-containing Neurons mentioning
confidence: 67%
“…Martinoli, P. Dubourg, M. Geffard, unpublished ob servations]. In addition, the pituitary receives fibers, not characterized ultrastructurally, and containing different peptides, such as corticotropin-releasing factor (CRF) or somatostatin, some of which likely originate from the pre optic region [19,30]: however, on the basis of in vivo and in vitro studies, there is no evidence for influences of cortico tropin-releasing factor or somatostatin on GTH secretion in goldfish [T. Marchant and R. Peter, unpublished results]. Cell bodies reacting to antibodies to tGnRH and projecting to the pituitary were also reported in the lateroventral pre optic region of the goldfish [24].…”
Section: Discussionmentioning
confidence: 99%
“…In birds the hypothalamic CRF system is quite similar to mammals, although the CRF-IR neurons extend far beyond the boundaries of the PVN proper (P6czely and Antoni 1984; Bugnon et al 1984;Yamada and Mikami 1985;Bons et al 1988;Ball et al 1989). In amphibians and fish this system, consisting of CRF-IR cells located in the preoptic nucleus, projects to the median eminence or neural lobe (Bugnon et al 1984;Olivereau et al 1984Olivereau et al , 1987Tonon et al 1985;Yulis and Lederis 1987;Olivereau and Olivereau 1988;Vallarino et al 1989).…”
Section: Crf Immunoreactivity In the Hypothalamo-hypophysial Systemmentioning
confidence: 99%
“…A hypothalamo-hypophysial portal system does not exist, and CRF acts in a paracrine fashion (Bugnon et al 1983;Olivereau et al 1984;Yulis and Lederis 1987;Olivereau and Olivereau 1988;Vallarino et al 1989). In amphibians, most CRF fibers end in the median eminence close to ACTH cells in the rostral pars distalis.…”
Section: Crf-ir Fibers In the Neural Lobe Of The Hypophysismentioning
confidence: 99%
See 1 more Smart Citation